Refusing to be Complicit in our Prison Nation: Teachers Rethinking Mandated Reporting - Meiners, Erica; Tolliver, Charity (Radical Teacher, 2016)
Ensuring that Black Lives Matter in schools requires seismic shifts including excavating the ongoing practices and policies that reproduce heterogendered white supremacy in schools. However, what is too often erased in these movements is the key way the profession of teaching facilitates racialized surveillance and criminalization. Teachers are mandated reporters who are required by law to report suspected negligence and abuse. While on paper this charge looks neutral, this essay illustrates why teachers should rethink their roles and organize against mandated reporting laws. To teach to ensure that all Black Lives Matter requires refusing to be complicit in the mechanisms that contribute to the destruction of too many families and communities.